The Study on the Factors That Affect Generation Y’s Impulsive Buying Behavior at Supermarket - Li, Song (2014)
The behavior of impulsive buying is a major research issue among customer behavior researchers, not only because of its complexities, but also its wide-spread prevalence over a broad range of product categories. Therefore, understanding consumers’ impulsive buying behavior is important for both the academic and business sectors. This study is to explore the relationship between promotional mix factors and impulsive buying behavior at supermarket. In this study, I will use four promotional mix factors which are advertising, sales promotion, personal selling and public relation as independent variables, while using impulse buying behavior as a dependent variable. Moreover, I will also add in two demographic factors as independent variables which are gender and race, so that I can better understand the relationship between consumers’ demographic backgrounds and impulse buying behavior. In this study, 400 questionnaires were sent out and the success rate was 75%. Through the multiple regressions analysis it was found that advertising and sales promotion has positive influence on generation Y’s impulse buying behavior. In addition, ANOVA analysis showed that consumers of various races differed in impulse buying behavior in the supermarket. Finally, the study will discuss conclusion derived from this research, its limitations and some recommendations for future research and for the benefit of supermarket retailers.